Implementasi CodeIgniter 4 untuk Pengelolaan Inventaris, Peminjaman dan Monitoring Mesin Berbasis Web di Laboratorium Pemesinan Politeknik Industri Logam Morowali - Abduh Malik Alfafa; Angga Tegar Setiawan; Kadex Widhy Wirakusuma (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
Machining laboratories play a crucial role in vocational education, particularly in supporting manufacturing practicums and research. However, manual inventory management and tool borrowing often lead to inefficiencies in record-keeping, maintenance delays, and inaccuracies in tracking tools and materials. This study aims to develop a web-based laboratory management system using the CodeIgniter 4 framework to enhance inventory management efficiency, streamline tool borrowing processes, and prepare for future IoT-based machine monitoring integration. The research employs an experimental development design approach. The system includes features for inventory management, tool and material borrowing, and a machine monitoring page designed for IoT integration. Built with PHP, MySQL, HTML, CSS, and JavaScript using the MVC architecture, the system has proven to improve inventory record-keeping efficiency, reduce borrowing errors, and facilitate real-time information access. Although successfully implemented, IoT integration for machine monitoring requires further development to provide real-time operational data. Additionally, enhancing system security through data encryption and two-factor authentication is necessary. This system significantly contributes to the digitalization of laboratory management, paving the way for smarter and more automated laboratories.